African folksongs as veritable resource materials for revitalizing music education in Nigerian schools (2013)
Some Yorùbá cultural values and expressions embedded in Egbeda-Egga women’s folksongs are the focus of this paper. With the use of in-depth interview and participant-observer methods, a collection, description and interpretation of some of the songs recorded during a field trip were undertaken. Analyses of the women’s repertoire reveal that immediate local environment are overlaid with folksongs which can serve as veritable resource materials useful for effective music teaching as well as tapping and honing learners’ artistic potentials to enhance and transform music performance in the classroom setting and beyond. The paper, therefore, submits that it is high time Nigeria embarked on school reforms and policies to make school music reflect the culture of the local communities.